Successive interference cancellation in tree algorithms of random multiple access - Vasilenko, Yu. A.; Tur, B. S. (Проблеми телекомунікацій, 2012)
Nowadays Wireless Broadband Networks (WBN) are dynamically developed sphere of science and technology. The given work is devoted to analysis of Random Multiple Access method called Successive Interference Cancellation (SIC), which is widely used in IEEE 802.16 standard. The direction of research is rather up-to-date and its importance is very high. We only use the Kalman filtering techniques to reduce distortion, which has a positive effect on the main index of the tree algorithms — the speed of conflict resolution. After analysis it is clear that among the various methods of random multiple access to the highest potential speed of conflict resolution have a tree algorithms using SIC. Potential SIC algorithms properties can be implemented in condition of the adjacent slots signal structure identity, one hundred is achieved by selecting amplitude — phase equalizers. An efficient algorithm for the amplitude and phase equalizer can be obtained, if taken into account the statistical structure of the received signals, taking into account the correlation of these signals on adjacent slots, the degree of coherence of the received signals, which directly determines the magnitude of the sampling step for transmitting a reference signal and the number of taps of the delay line.
Keywords: tree algorithm; interference; polynomial Volterra; radio channel; Kalman-Bucy filter